Impact of the acute local inhibition of soluble epoxide hydrolase on diabetic skin microcirculatory dysfunction. (November 2019) - Savina, Yann; Duflot, Thomas; Bounoure, Frederic; Kotzki, Sylvain; Thiebaut, Pierre-Alain; Serreau, Pierre-Alex; Skiba, Mohamed; Picquenot, Jean-Michel; Cornic, Marie; Morisseau, Christophe; Hammock, Bruce; Imbert, Laurent; et al.
The impact of the local inhibition of soluble epoxide hydrolase, which metabolizes vasodilator and anti-inflammatory epoxyeicosanoids, on diabetic skin microvascular dysfunction was assessed. In diabetic db/db mice, basal skin blood flow assessed using laser Doppler imaging was similar to that of control mice, but thermal hyperemia was markedly reduced. At 2 h after the topical administration of an aqueous gel containing the soluble epoxide hydrolase inhibitor trans-4-[4-(3-adamantan-1-yl-ureido)-cyclohexyloxy]-benzoic acid (t-AUCB: 400 mg/L), the peak concentration of t-AUCB was detected in the skin of diabetic mice, which quickly decreased thereafter. In parallel, 2 h after application of t-AUCB treatment, thermal hyperemia was increased compared to the control gel. Quantification of t-AUCB in plasma of treated animals showed no or low systemic diffusion. Furthermore, haematoxylin and eosin histological staining of skin biopsies showed that skin integrity was preserved in t-AUCB-treated mice. Finally, for pig ear skin, a surrogate for human skin, using Franz diffusion cells, we observed a continuous diffusion of t-AUCB from 2 h after application to beyond 24 h. A single topical administration of a soluble epoxide hydrolase inhibitor improves microcirculatory function in the skin of db/db mice and might represent a new therapeutic approach for preventing the development of skin complications in diabetic patients.